Damage Detection in Frame Structure Using Piezoelectric Actuator. (2017) - Patil, Chetan S.; Roy, Sajal; Jagtap, K.R.
Abstract: Health-monitoring and On-line damage detection techniques on frame structures are stronglyneeded.Vibration based methods with piezoelectric sensor and actuator integrated into structures is a promising option to fulfil such requirements. This paper presents use of piezoelectric actuator to detect bolt loosening in a frame structure. Frequency response function (FRF) method is used along with piezoelectric actuator. These methods utilize finite element analysis techniques, together with to detect damage. They locate and estimate damage by comparing dynamic responses between damaged and undamaged structures. AFrame structure is modelled using finite element software ABAQUS. Frame structure is coupled with piezoelectric actuator which excites the structure for transient analysis. Acceleration responses are measured at various points in structure and this data is used to find out frequency response functions (FRF). The shift in the natural frequencies of the structure is observed for undamaged and damaged structure to detect the damage.